Penerapan Customer Relationship Management Terhadap Kepuasan Pelanggan Pada Laundry Sabana Tanjungpinang - Nopianti, Rosmita; Putri, Rosa Eka; Alfitrah, Putri Anggraini; Syahputro, Satrio Bimo (Universitas Tabanan, 2023)
Customer Relationship Management (CRM) is a long-term business strategy aimed at building and maintaining strong relationships with customers. Through the effective implementation of Customer Relationship Management (CRM), customer satisfaction can be enhanced. This research aims to evaluate the utilization of Customer Relationship Management (CRM) in Sabana Laundry business with the objective of improving customer satisfaction. The respondents in this study are customers of Sabana Laundry, selected through purposive sampling method. Data analysis is conducted using qualitative analysis methods. This approach involves in-depth interviews with the owner, employees, and customers of Sabana Laundry, direct observation of operational processes, and analysis of documents related to the implementation of Customer Relationship Management (CRM). The results of the analysis indicate that the implementation of Customer Relationship Management (CRM) has a significant positive impact on customer satisfaction levels. Therefore, it can be concluded that Customer Relationship Management (CRM) holds substantial potential for enhancing customer satisfaction in the context of Sabana Laundry business.